THE VALIDITY OF THE COLLUSIVE TENDER IN THE PROCUREMENT OF GOODS AND SERVICES OF BUS TRANSJAKARTA Pte Ltd. (Case Study the Verdict Number: 15/KPPU-I/2014) - Adella, Bella Rihandita (Yustisia, 2018)
Conspiracy in the tender including auction collusive tenders occuring through a deal between businessmen, between the owner of the work as well as between the two parties. The tender conspiracy case that happened in Indonesia is a case involving the Pte Ltd. Industri Kereta Api (Pte Ltd. INKA) in the procurement of Transjakarta fiscal of 2013. From the results of this research noted that enforcement of the law against the procurement of Transjakarta yet running optimally, where knowing the verdict matter passengers number: 15/KPPU-I/2014 in unfair business competition elements Law number 5 of 1999 can't show anyone others who benefited by Pte Ltd. INKA and profitable, as well as in the By Law 16 of Number 2018 on The President of Government procurement of goods/service stating Pte Ltd. INKA is not proven procurement tenders because collusion Pte Ltd. INKA do not know reasons of Pte Ltd. Mayapada Auto Sempurna resign therefore the Pte Ltd. INKA as winner in the tender Package I repeated Single Bus.